The Relationship Between Authentic Leadership, Performance and Intention to Quit the Job of Nurses. Issue 3 (3rd July 2019) - Özer, Özlem; Uğurluoğlu, Özgür; Sungur, Cuma; Çirakli, Ümit
Abstract: This study examines the relationships between of nurses' perception of their authentic leadership, intention to quit, and employee performance. The implementation part of the study was conducted with nurses working in a public hospital in the city of Yozgat, Turkey. The data were collected in December 2017 from 189 participants. The results of the analyses showed that relationships between authentic leadership dimensions and intention to quit were not significant. While the all dimensions of authentic leadership explained 6.8% of the variance for the employee performance; explained 3.7% of the variance for the intention to quit. According to these results, improving authentic leadership perception of nurses will improve nurse performance.